The nature and context of Kaaps: a contemporary, past and future perspective - Hendricks, Frank (Multilingual Margins: A journal of multilingualism from the periphery, 2018)
In this contribution, which serves as orientation for this special edition, the accent falls chiefly on the contemporary manifestation of Kaaps as colloquial variety of Afrikaans, but also on its historic roots and the challenges regarding its future. Besides a reflection on the name â€œKaapsâ€ and other alternative names, this language form is described with reference to its origin, traditional speakers, geographic situation, sociolectic nature, linguistic character and its contextual usages. Kaaps is presented as a variety of the dialect group Southwestern Afrikaans which as a form of colloquial Afrikaans refers back historically to the seventeenth century influence of slaves on the formation of Afrikaans and which is currently chiefly manifested as a sociolect associated with the working class of the Cape Peninsula. The social assessment, lingua-political treatment and survival potential of this variety are also reviewed.